Aplicação e os efeitos da política de reserva de vagas na UNESP - Aversente, Lucas [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
This course conclusion work deals with an analysis of the application of the vacancy reservation policy at the Universidade Estadual Paulista Júlio de Mesquita Filho (UNESP). As objectives, we will investigate how the policy has been affecting the profile of UNESP's students, if support policies such as the permanence policies are adapting to the increase in students who need them, if students enrolled by the vacancy reservation system have academic success equivalent to those of the universal admission system and, finally, a brief essay on the power and resistance of postgraduate vacancy reservation policies. For these purposes, we will start by exploring the vestibular mechanism as a social funnel and the effects of the reservation of vacancies, and then discuss the need for permanence policies for non-avoidance and quality of learning for university students in economic and social vulnerability, to understand how they are structured the student permanence policies at UNESP, what were their strategies and actions in the face of the new dynamics imposed by the reservation of vacancies and finally we will analyze the functioning of the selection in the graduate and the power that involves this stage of higher education. The vacancy reservation policy is within what we know as affirmative action policies. Affirmative action policies are mechanisms of historical reparation for marginalized and wronged groups, which focus mainly on education and the world of work, betting on these policies as ways to reduce racial and social inequalities. It was possible to conclude that, in general, the presence of students enrolled by the vacancy reservation system did not decrease the quality of the university, and, contrary to what was thought, it decreases the dropout rates of UNESP.

O presente trabalho de conclusão de curso trata de uma análise da aplicação da política de reserva de vagas na Universidade Estadual Paulista Júlio de Mesquita Filho (UNESP). Como objetivos investigaremos como a politica vem afetando o perfil do estudante da UNESP, se as políticas de suporte como o caso das politicas de permanência estão se adequando ao aumento de alunos que necessitam das mesmas, se os alunos matriculados pelo sistema de reserva de vagas tem sucesso acadêmico equivalente aos do sistema universal de ingresso e por fim um breve ensaio sobre a potência e a resistência das politicas de reserva de vagas na pós-graduação. Para tais objetivos iniciaremos explorando o mecanismo do vestibular como funil social e os efeitos da reserva de vagas, para depois discutir a necessidade das políticas de permanência para a não evasão e qualidade de aprendizado para o público universitário em vulnerabilidade econômica e social, entender como estão estruturadas as políticas de permanência estudantil na UNESP, quais foram as suas estratégias e ações frente a nova dinâmica imposta pela reserva de vagas e por último analisaremos o funcionamento da seleção na pós-graduação e o poder que envolve essa etapa do ensino superior. A política de reserva de vagas está dentro do que conhecemos como políticas de ações afirmativas. As políticas de ações afirmativas são mecanismos de reparação histórica, para grupos marginalizados e injustiçados, que tem seu foco principalmente na educação e no mundo do trabalho, apostando nessas políticas como formas de se diminuir as desigualdades raciais e sociais. Foi possível concluir que de forma geral a presença dos alunos matriculados pelo sistema de reserva de vagas não diminuiu a qualidade da universidade, e ao contrario do que se pensava diminui os índices de evasão da UNESP.
Application and effects of the reservation policy vacancies at UNESP
Keywords: Reserva de vagas; UNESP; Permanência estudantil; Politica de ação afirmativa; UNESP; Reservation of vacancies; Student permanence; Affirmative action policy